Prod-users of geospatial information: some legal perspectives. Issue 2 (4th May 2019) - Cho, George; Crompvoets, Joep
Abstract: Producers and users (prod-users) volunteer, contribute and use geospatial information (GI) for a variety of mapping, documentary and other applications. The paper outlines some legal perspectives of crowd-sourced information by addressing general problems of the legal rights and obligations of volunteers and users. The volunteered geographic information (VGI) model is discussed within the meaning of Web 2.0 and understanding the risks of legal liability and responsibilities. Part of this understanding is an application of the role of the quality of VGI when contrasted with the OpenStreetMap experience. Ownership issues and the legal responsibilities of prod-users are discussed together with the special case of Good Samaritans. Proposed governance structures that could be developed across various countries that have engaged with VGI and prod-users are then suggested. It is concluded that current legal structures may no longer be appropriate to accommodate legal and regulatory mechanisms that may be helpful for governments, industry and prod-users.